Thermally assisted healable film based on modified natural rubber-bearing benzyl chloride functionality - Rattanawadee Ninjan; Bencha Thongnuanchan; Natinee Lopattananon; Subhan Salaeh; Anoma Thitithammawong (eXPRESS Polymer Letters, 2024)
This work reported a practical approach to turning conventional natural rubber (NR) into a thermally healable rubber. 4-vinylbenzyl chloride was first polymerized in the NR latex to yield graft copolymers of NR and poly(vinylbenzyl chloride), NR-g-PVBC. The cutting and rejoining process was used to study the healing ability of latex film. The healing behavior was observed after the reassembled film was heated at 100 °C for 1 h and then allowed to heal continuously at room temperature (RT). The healed film displayed a 58.44% regain of the tensile strength (4.57 MPa) after being allowed to recover at RT for 72 h. Additionally, the chloromethyl moieties in the NR-g-PVBC could be converted into quaternary ammonium (QA) groups by reaction with trimethylamine, producing the quaternized NR-g-PVBC (NR-g-QPVBC). Ionic crosslinking of the NR-g-QPVBC film was achieved by incorporating sodium tripolyphosphate (STPP). The latex film had a tensile strength of 15.32 MPa and could withstand a strain of 868% when ionically cured with 2 phr of STPP. After the healing process, the cured film showed a healing efficiency of 49.67% in tensile strength (7.61 MPa). Furthermore, a suturing test was performed to investigate the feasibility of developing a suture training pad from the corresponding cured film. The film’s ability to heal with heat assistance was its significant practical advantage, enhancing its realism and mimicking the healing process in human skin.